2012
DOI: 10.5539/ass.v8n15p184
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Social Responsibility of Corporations in China

Abstract: It is the consensus of the Chinese enterprises to focus on the sustainable development of enterprises and society and emphasize responsibility and contribution. Compared with the large and medium-sized enterprises, the small and medium enterprises (SME) have fulfilled certain social responsibility and played an irreplaceable role in promoting economic growth, increasing employment, technological innovation and social harmony and stability. However, there are some problems for corporation of China to fulfill th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As observed by Wang et al (2010), the overall level of CSR reporting was not high, and both the breadth and depth of the disclosure were insufficient to satisfy stakeholders' requirements. Qi et al (2012) emphasized that CSR was not only the responsibility of enterprises but also that of the government, media and consumers. Furthermore, Debeljak et al (2011) identified some elements of CSR insincerity in every company during its early stage of acquiring CSR practices, especially during the beginning of the development of business culture.…”
Section: Introductionmentioning
confidence: 99%
“…As observed by Wang et al (2010), the overall level of CSR reporting was not high, and both the breadth and depth of the disclosure were insufficient to satisfy stakeholders' requirements. Qi et al (2012) emphasized that CSR was not only the responsibility of enterprises but also that of the government, media and consumers. Furthermore, Debeljak et al (2011) identified some elements of CSR insincerity in every company during its early stage of acquiring CSR practices, especially during the beginning of the development of business culture.…”
Section: Introductionmentioning
confidence: 99%
“…The ISO 26000 standard, which promotes the acceptance of social responsibility around the world, describes the view of social responsibility and the standards that should be followed and contributes to the achievement of long-term development goals, particularly for sustainable development (Puneet and Ashish, 2012). It has been demonstrated in numerous studies that social responsibility is essential for stimulating economic growth while also increasing employment, technological innovation, social harmony, and stability (Certo and Certo, 2012;Qi et al, 2012).…”
Section: Review Literaturementioning
confidence: 99%